1970
DOI: 10.1126/science.168.3936.1220
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Allergic Encephalomyelitis: Synthesis of Disease-Inducing Site of the Basic Protein

Abstract: A highly encephalitogenic peptide whose structure resembles the sequence of amino acids surrounding the single tryptophan residue in the encephalitogenic A1 protein from bovine myelin was synthesized. This peptide is similar in the sequence to peptic peptide E and tryptic T27, derived directly from the A1 protein, and is as active on a molar basis as the A1 protein. The major disease-inducing site of the A1 protein resides in a linear sequence of nine amino acids: H-Phe-Ser-Trp-Gly-Ala-Glu-Gly-Gln-Lys-OH. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
56
0
1

Year Published

1971
1971
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(57 citation statements)
references
References 19 publications
0
56
0
1
Order By: Relevance
“…This protein represents 30% of the total protein present in central nervous system myelin [see Braun (1984)] and is the factor responsible for the induction of experimental allergic encephalomyelitis (Eylar et al, 1970). The molecular mechanism of this pathological activity is not precisely known, but the location of the protein on the cytoplasmic side of the myelin membrane and its binding to the membrane surface suggest that the MBP stabilizes the multilamellar compact structure by joining the apposed surfaces of the myelin plasma membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This protein represents 30% of the total protein present in central nervous system myelin [see Braun (1984)] and is the factor responsible for the induction of experimental allergic encephalomyelitis (Eylar et al, 1970). The molecular mechanism of this pathological activity is not precisely known, but the location of the protein on the cytoplasmic side of the myelin membrane and its binding to the membrane surface suggest that the MBP stabilizes the multilamellar compact structure by joining the apposed surfaces of the myelin plasma membranes.…”
mentioning
confidence: 99%
“…The molecular weight of the protein is 18.4K, and, together with the proteolipid protein of molecular weight 25K, it constitutes approximately 80% by weight of the total protein in myelin [see Boggs and Moscarello (1 978a) and Boggs et al (1982a)I. Several physicochemical investigations on the structure of the MBP have shown that the protein is devoid of tertiary structure in aqueous solutions (Eylar & Thompson, 1969;Chao & Einstein, 1970;Palmer & Dawson, 1969) but assumes highly ordered conformations in organic solvent mixtures (Liebes et al, 1975;Stone et al, 1985) and upon Abbreviations: DMPG, 1,2-dimyristoyl-sn-glycero-3-phosphoglycerol; DMPC, 1,2-dimyristoyl-sn-glycero-3-phosphocholine; DPPG, 1,2-dipalmitoyl-sn-glycero-3-phosphoglycerol; ESR, electron spin resonance; MBP, bovine spinal cord myelin basic protein; n-PGSL, I-acyl-2-[n-(4,4-dimethyloxazolidine-N-oxyl)stearoyl]-sn-glycero-3-phosphoglycerol; Tris, tris(hydroxymethyl)aminomethane; EDTA, ethylenediaminetetraacetic acid.…”
mentioning
confidence: 99%
“…In 1970 I synthesized and chemically defined the requirements for EAE induction from the first myelin basic protein encephalitogenic sequence (8,43,47). The contribution of each of the nine amino acids to immunity was ascertained.…”
mentioning
confidence: 99%
“…EAE is also the only experimental autoimmune disease for which the exact amino acid sequence of an inciting molecule, basic protein of myelin, is known (1). Nearly identical basic proteins are found in all mammalian myelin studied and an encephalitogenic nonapeptide fragment of the bovine basic protein, which has been both isolated and synthesized de novo, has been shown to be encephalitogenic on a molar basis at least equivalent to the 170 amino acid basic protein (2). Thus, EAE also provides an attractive model for studying the immunological mechanisms of autoimmune diseases in general.…”
mentioning
confidence: 99%